C-Peptide Levels Predict the Effectiveness of Dipeptidyl Peptidase-4 Inhibitor Therapy - Sevin Demir; Sule Temizkan; Mehmet Sargin (Journal of Diabetes Research, 2016)
Background. Our aim was to define the conditions that affect therapeutic success when dipeptidyl peptidase-4 (DPP-4) inhibitor is added to metformin monotherapy. Materials and Methods. We reviewed the medical records of 56 patients who had received DPP-4 inhibitor as an add-on to metformin monotherapy and evaluated their response in the first year of therapy. Fasting blood glucose (FBG), HbA1c, C-peptide, and weight of the patients were recorded at 3-month intervals during the first year of treatment. Results. Patients who added DPP-4 inhibitor to metformin monotherapy had significant weight loss (P=0.004) and FBG and HbA1c levels were significantly lowered during the first 6 months (both P<0.001). Baseline levels of C-peptide were predictive for success of the treatment (P=0.02), even after correction for confounding factors, for example, age, gender, or BMI (P=0.03). Duration of diabetes was not a predictor of response to treatment (P=0.60). Conclusion. Our study demonstrates that in patients having inadequate glycemic control, the addition of a DPP-4 inhibitor as a second oral agent to metformin monotherapy provides better glycemic control, protects β-cell reserves, and does not cause weight gain. These effects depend on baseline C-peptide levels.